Life under another Sun: From Science Fiction to Science. (2nd October 2019) - Gillon, Michaël
Abstract : Initiated in the sixteenth century, the Copernican revolution toppled our Earth from its theological pedestal, revealing it not to be the centre of everything but a planet among several others in orbit around one of the zillions of stars of our Universe. Already proposed by some philosophers at the dawn of this major paradigm shift, the existence of exoplanets, i.e. planets in orbit around stars other than our Sun, remained suspected but unconfirmed for centuries. It is only in the last decade of the twentieth century that the first of these extrasolar worlds were found. Their seminal discoveries initiated the development of more and more ambitious projects that led eventually to the detection of thousands of exoplanets, including a few dozen potentially habitable ones, i.e. terrestrial exoplanets that could harbour large amounts of liquid water – and maybe life – on their surfaces. Upcoming astronomical facilities will soon be able to probe the atmospheric compositions of some of these extrasolar worlds, maybe performing in the process the historical detection of chemical signs of life light-years away. But while the existence of extraterrestrial life remains pure speculation for now, it has been a major theme of science fiction for more than a century. By creating countless stories of encounters between humans and alien forms of life, science-fiction authors have pursued, in a sense, the Copernican revolution, confronting us with the idea that not only could life be widespread in the Universe, but also that our species may be far from the Cosmic pinnacle in matters of intelligence and technological development.